Estimate model of system management for database security - W. Ch Alisawi; Alaa Abdul AlMuhsen Hussain; Wasan A. Alawsi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
A generalized model of information protection of a database management system is proposed, which can be used to implement database protection under any database management system. This model development methodology consists of four stages: requirements gathering, database analysis, “multi-level relational logical construction and a specific logical construction. The first three steps define actions for analyzing and developing a secure database, thus creating a generalized and secure database model”.